Advantages and Hygienic Benefits of Partial Removable Dentures - Hajiyev J.G.; Arkhmammadov A.M; Ahmadov S.I. (American Journal of Biology and Natural Sciences, 2025)
The cast metal framework denture (metal removable partial denture prosthesis) belongs to the group of removable dentures and is considered more advanced and comfortable compared to alternative removable denture types. These dentures are convenient to use, do not interfere with eating, do not alter the sense of taste, and are both reliable and long-lasting. A cast metal framework denture differs from standard acrylic dentures by having a more sophisticated framework made of metal. Artificial teeth and the main base, consisting of acrylic material, are attached to this metal framework. The unique feature of this construction is its minimal volume, which makes the prosthesis almost unnoticeable when worn in the mouth. Main advantages of cast metal framework dentures: For the upper jaw, the prosthesis does not include a thick plastic plate that covers almost the entire palate. Instead, a thin metal arch is used. This design does not interfere with speech or affect the sense o• The lower jaw version of the framework denture also has minimal volume while providing stable fixation and not disturbing speechf taste. The lower jaw version of the framework denture also has minimal volume while providing stable fixation and not disturbing speech. The recommended usage period for a cast metal framework denture is 5 years, while standard acrylic dentures are advised to be replaced every 2 years. The reason is that acrylic dentures exert greater pressure on the gum tissue, leading to faster atrophy and changes in the prosthetic bed. As a result, the denture no longer fits properly, causing discomfort, pain, and reduced retention in the oral cavity.